Studi Literatur tentang Adab Siswa terhadap Guru: Implikasi Psikologis, Sosial, dan Pendidikan - Hamim Thohari; Sambang Pangesthi; Putri Dwi Naryaningsih (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
Student manners towards teachers are very important in education because they ensure an effective and peaceful learning environment. Good manners, such as respect, politeness, and responsibility, affect the relationship between teachers and students from various psychological, social, and educational aspects of the learning process. From a psychological perspective, good student manners can reduce stress and improve teachers' mental well-being. Research shows that positive and respectful relationships between teachers and students can increase teachers' job satisfaction and reduce their stress levels (Pianta, R. C., & Stuhlman, M. W, 2004). On the other hand, non-compliance and negative behaviors from students can frustrate teachers and demotivate them, which in turn can have a negative impact on the overall classroom atmosphere. Good manners from students help teachers create a more supportive and conducive environment for good mental health (Johnson, S. M., & Birkeland, S. E. (2003). Good student manners, such as respect and empathy, are important in their daily social interactions. Lickona (1991) has conducted a study showing that character education, which includes lessons on manners and ethics, can improve positive social relationships and reduce antisocial behavior in schools. Therefore, student behavior can affect their relationships with teachers, classmates, and the school community as a whole.From an educational perspective, good student manners are also closely related to how effective learning takes place. Having an attitude of respect and obedience to educators can increase student engagement and motivation in learning. Good student manners can improve academic outcomes and educational achievement of students in the classroom (Emmer and Evertson, 2016). In other words, good student manners can help create a more productive learning atmosphere and reduce distractions that can interfere with the learning process. This study aims to determine how student manners affect the three psychological, social, and educational aspects of student manners towards teachers. This study will investigate various sources and results related to student manners and their implications, and provide suggestions for the best methods to improve educational practices.